Habitat or prey specialization in predatory ladybird beetles: a case study of two closely related species. (16th June 2015) - Ferrer, A.; Dixon, A. F. G.; Hemptinne, J.‐L.
Abstract: This study examines the niche and diet breadth of two closely related sympatric aphidophagous ladybirds: Adalia decempunctata and A. bipunctata . The degree of habitat specialization of these species is investigated, and its effect on life history traits of females is explored. The importance of prey quality in determining the diet breadth is also examined. The niches occupied by these species in three countries, the UK, Belgium and southern France, are similar: A. decempunctata is an arboreal habitat specialist with a narrower set of prey than A. bipunctata, which is commonly found on several types of vegetation. The niches of the two species overlap on trees. Experiments indicate that habitat specialization has resulted in A. decempunctata investing more in each of its offspring than A. bipunctata . A. decempunctata females lay, relative to their body size, heavier eggs than those of the more generalist A. bipunctata, which results in A. decempunctata having bigger larvae. In addition, A. decempunctata larvae are better at surviving starvation than A. bipunctata larvae. In contrast to the expected pattern in food specialization, our study failed to demonstrate a better efficiency of the specialist when fed its usual prey and a detrimental effect when fed on prey that it is unlikely to encounter in the field. The reproductive performance of the specialist ladybird was better when fed an aphid that it was unlikely to regularly feed on in the field. Therefore, the narrow diet of the specialist ladybird is most likely a consequence of it occupying a narrow habitat rather than the quality of the prey. Although further studies on specialization in predatory insects are needed, the results indicate that unlike the role of plant quality in host specialization in herbivorous insects, prey quality has not been the main determinant of ecological specialization in these predatory insects.